Exploring Lived Experiences of Expatriate Teachers: A Phenomenological Study of Chinese Language Teachers at a Private School in Thailand - Yang, Yaqi; Saengboon, Saksit (Arts of Management Journal, 2025)
The growing global demand for Chinese language education has positioned Thailand as a pivotal hub in Southeast Asia due to its robust educational exchanges with China. However, Chinese language teachers (CLTs) in Thai private schools face significant challenges adapting to this unique cultural and institutional environment. This study explores the lived experiences of five CLTs in Thailand, focusing on their navigation of cultural, linguistic, and structural barriers within high power-distance and collectivist settings. Using a phenomenological qualitative methodology supported by Byram’s Intercultural Communicative Competence (ICC) model and Hofstede’s Cultural Dimension Theory (CDT), the research employs semi-structured interviews and thematic analysis to uncover key insights. Findings highlight CLTs' challenges, including restricted pedagogical autonomy, cultural adaptation struggles, and work-life balance issues. Yet, the study also reveals how marginalization paradoxically fosters pedagogical innovation and autonomy, enabling teachers to adapt their teaching practices creatively. These insights underscore the urgent need for Thai educational institutions to develop supportive policies that enhance intercultural communication, professional integration, and the well-being of foreign educators. This study contributes to Thai education by addressing the gaps in understanding the adaptation of CLTs in non-Western contexts, offering actionable insights for administrators and policymakers to foster an inclusive and effective teaching environment. By advancing theoretical frameworks and practical solutions, the research highlights its relevance in enhancing Thailand’s role as a leader in multicultural education and its efforts to integrate international teachers effectively.